2008
DOI: 10.1136/bjo.2007.137075
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with verteporfin for age-related macular degeneration or polypoidal choroidal vasculopathy: comparison of the presence of serous retinal pigment epithelial detachment

Abstract: In eyes with typical AMD, a serous PED was associated with a significant decline in BCVA compared with eyes without a serous PED. In eyes with PCV, the visual outcomes were unaffected by a serous PED. When PDT is administered, differentiating PCV from typical AMD using indocyanine green angiography is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…PDT combined with anti-VEGF therapy is currently recommended for treatment of PCV and was reported to have good visual outcome in patients suffering from PCV. [22][23][24][25] However, relatively few studies have investigated the visual prognostic factors following PCV treatments, [26][27][28][29][30] especially the predictive factors following combined therapy. Some of the clinical factors such as age, baseline best-corrected visual acuity and size of haemorrhage, and presence of PED were reported to govern the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…PDT combined with anti-VEGF therapy is currently recommended for treatment of PCV and was reported to have good visual outcome in patients suffering from PCV. [22][23][24][25] However, relatively few studies have investigated the visual prognostic factors following PCV treatments, [26][27][28][29][30] especially the predictive factors following combined therapy. Some of the clinical factors such as age, baseline best-corrected visual acuity and size of haemorrhage, and presence of PED were reported to govern the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, PDT with verteporfin resolves the polypoidal lesions with high prevalence in PCV eyes. 9,10 However, longer follow-up studies of PDT of 2 or 3 years have reported that the VA decreased at the final visit. [24][25][26] It is well known that PDT cannot resolve the branching Figure 1 The diagram shows the retreatment criteria in the current study after month 3 (3 months after treatment).…”
Section: Discussionmentioning
confidence: 99%
“…21 The increased subretinal hemorrhages after PDT for patients with PCV is a well-known complication with incidence rates from 18 to 30%. 10,11,20 While the current study had a small number of cases, subretinal hemorrhages did not occur during 24 months. In conclusion, the current study showed that IVR injections were effective for maintaining or improving VA and the anatomic changes in patients with PCV with recurrent or residual exudation from branching vascular networks without adverse events over 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations